Determination of the Relative Configuration of β‐Amino Acid Esters Based on Residual Dipolar Couplings. Issue 31 (2nd October 2015) - Niklas, Thomas; Steinmetzger, Christian; Liu, Weiping; Zell, Daniel; Stalke, Dietmar; Ackermann, Lutz; John, Michael
Abstract: Configurational and conformational characterization of two synthetic β‐amino acid esters comprising an indan motif was achieved by residual dipolar couplings. We further observed that the stability of Q factors upon addition of structural noise substantially facilitates the selection of the "correct" structure. The two analyzed compounds differ by a single methyl group, which leads to a remarkable conformational change. Abstract : Two synthetic β‐amino acid esters comprising an indan motif were structurally characterized by residual dipolar couplings. We demonstrate that the stability of Q factors against structural noise substantially facilitates the verification process. The "correct" structures differ by a single methyl group, which leads to a remarkable conformational change.